Answer:
243
Step-by-step explanation:
its all about laws of exponent
pls open the pic for ur answer
i hope it may have helped u
Answer:
a:500 b:547,500 c:557,500
Step-by-step explanation:
Answer:
The amount that came is ![\frac{-68}{3}](https://tex.z-dn.net/?f=%5Cfrac%7B-68%7D%7B3%7D)
Step-by-step explanation:
The computation is shown below:
According to the question, it is mentioned that
Multiply 4 by ![-5\frac{2}{3}](https://tex.z-dn.net/?f=-5%5Cfrac%7B2%7D%7B3%7D)
First open the equation in a fraction it would be ![\frac{-17}{3}](https://tex.z-dn.net/?f=%5Cfrac%7B-17%7D%7B3%7D)
Now multiplied the above fraction by a 4
That gives the result of ![\frac{-68}{3}](https://tex.z-dn.net/?f=%5Cfrac%7B-68%7D%7B3%7D)
Hence, the amount that came is ![\frac{-68}{3}](https://tex.z-dn.net/?f=%5Cfrac%7B-68%7D%7B3%7D)
We simply multiply the 4 with the given fraction
Thus the above represents the simplest form of the fraction
Answer:
Let x represents the Sara eat pancake and y represents the Phil eat the pancake.
As per the statement:
Phil ate three less than twice as many pancakes as Sara.
"Twice as many pancake as Sara" means 2x
"three less than twice as many pancakes as Sara" means 2x -3
⇒
.....[1]
It is also given that together they combined to eat 15 pancakes.
⇒
.....[2]
Substitute equation [1] into [2] we get;
![x+2x-3 = 15](https://tex.z-dn.net/?f=x%2B2x-3%20%3D%2015)
Combine like terms;
3x-3 =15
Add 3 to both sides we get;
3x = 18
Divide both sides by 3 we get;
x = 6
Substitute the value of x in [1] we get;
y = 2(6)-3 = 12-3 =9
y = 9
Therefore, the pancakes did each eat are;
Sara eat pancake = 6 and Phil eat pancake = 9